Sports sponsorship - Kelly, Jim (Henry Stewart Talks, 2009)
Sponsorship strategy, The model partnership, AIB and the Ryder Cup, Rationale, Strategic objective, Communications plan, The visual thread, Localizing communications and keeping it relevant, Regional Ryder Cup roadshow, Relevancy to customers, Relevancy to staff, Results